Pengaruh Audit Manajemen, Komitmen Organisasional Manajer, dan Pengendalian Internal Terhadap Penerapan Prinsip-Prinsip Good Corporate Governance - Mu'amar, Mu'amar; Syam, Dhaniel; Zubaidah, Siti (Jurnal Reviu Akuntansi dan Keuangan)
This study aims to examine the effect of Management Audit, Organizational CommitmentManager, Internal Control Against Application of Principles of Good Corporate Governance. Thesample of this study is 62 manufacturing companies listed in Indonesia Stock Exchange (BEI) in2013 with purposive sampling technique.. The data was analized with logistic regression. Theresult showed that management audit has no effect on the implementation of good corporategovernance principles, organizational commitment of managers has an effect on the applicationof the principle of good corporate governance, and internal control does not affect the implementation of good corporate governance principles.Ke yword: Management Audit, Organizational Commitment Manager, Internal Control, Principles of Good Corporate Governance.